Challenges in learning for company‘s financial viability assessment and management - Koleda, Nadezda; Oganisjana, Karine (Business: Theory and Practice, 2015)
Many entrepreneurs in Latvia are limited in choice of tools for the improvement of their financial literacy. Therefore the training course “Financial literacy of entrepreneurs in the field of financial viability management” was elaborated and tested with the aim to improve the course and reveal the challenges facing different categories of learners. The research was formative as it combined the promotion of learners and trainers’ competencies and behaviours with the research process throughout all the five training cycles. The research methods applied were chosen based on the inner logics and aims of the teaching and learning processes: videorecording of learners’ activities and analysis of the videomaterials; analysis of the learners’ work and reflections. Out of the identified sixteen challenges faced by learners, three were especially crucial and caused further difficulties in coping with different tasks on assessment and management of company’s financial viability. It was concluded that there may be three categories of learners whose training should be organised in different modes taking into account the level of their preparedness in accountancy, tax accounting and financial analysis.